Love, Sex and Racism in Charles Chesnutt’s Selected Narratives - Dahal, Madhab Prasad (The Saraswati Review, 2024)
The light-skinned mulattoes in the slavery era in the US employed various techniques of masking their personalities to revolt against the racist society. Besides gaining freedom, masking had a psychological reason related to sexuality which played a vital role by influencing people to fall in love or hate with each other. This study explores some psychological factors that inspired African Americans to mask their identity in Charles Waddell Chesnutt’s two stories: The Wife of His Youth (1898), and The House behind the Cedars (1900). Based on the two stories, the article shows how some white and black members of the post-Civil War period were subservient to their libidinal desires. It uses the Freudian model that unfolds repressed desires revealed on the surface in different forms like dreams and speeches, Stephen W. Simpson’s and Bert Olivier’s insight on the need for adjustment between sexuality and civilization. It makes a thematic analysis of these narratives by employing a psychoanalytical perspective. The finding of the paper unfolds that besides the Negro slaves’ longing for emancipation from slavery, masking had a physical reason related to sexuality. It affirms that their libidinal desires were responsible for leading them to work against their legacy. This study contributes in the fi eld of scholarship by introducing a new parameter of interpretation.